Modified ABS (Acrylonitrile Butadiene Styrene) resin and preparation method thereof

Through the ratio and preparation method of modified ABS resin, the problems of insufficient flame retardancy, contradiction between impact resistance and rigidity, and poor weather resistance of traditional ABS resin are solved, and efficient flame retardancy, optimized mechanical properties and significantly enhanced weather resistance are achieved.

CN120137343APending Publication Date: 2025-06-13DANYANG MEIHUA NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510431169.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

Traditional ABS resins have problems such as insufficient flame retardancy, contradiction between impact resistance and rigidity, and poor weather resistance.

Method used

Modified ABS resin is used, including ABS matrix resin, silicone modified acrylate core-shell toughener, phosphorus-nitrogen-based composite flame retardant, nano-grade titanium dioxide, rare earth beta nucleating agent and hindered amine light stabilizer. The temperature is controlled in sections through the fluidized bed activated flame retardant and the twin-screw extruder to ensure uniform dispersion of components and interface compatibility.

Benefits of technology

It achieves high-efficiency flame retardant (UL94 V-0 to V-1 levels), suppresses melting droplets, reduces the impact on mechanical properties, improves low-temperature impact resistance, tensile strength and toughness, optimizes coordinated flame retardant and mechanical properties, and significantly enhances the weather resistance and surface finish of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120137343A_ABST
    Figure CN120137343A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ABS resin, and discloses modified ABS resin and a preparation method thereof.The modified ABS resin adopts a phosphorus-nitrogen flame retardant compounded by aluminum hypophosphite and melamine polyphosphate, dispersity is improved through surface modification of a silane coupling agent, efficient flame retardance is achieved, molten drops are inhibited, the influence on mechanical performance is reduced, and the flame retardance is improved. The low-temperature impact resistance is improved through the organic silicon modified acrylate core-shell toughening agent, meanwhile, rigidity loss is avoided, the tensile strength (larger than or equal to 45 MPa) and toughness are balanced, and the synergistic flame retardance and mechanical performance are optimized; nano titanium dioxide is subjected to double coating of stearic acid and silane and ultraviolet pretreatment, so that dispersity and ultraviolet shielding performance (UVA transmittance lt; the strength retention rate of the material is larger than or equal to 90% after the material is subjected to QUV aging for 1000 hours in combination with the hindered amine light stabilizer (HALS), the crystal structure is optimized through the rare earth beta nucleating agent, the thermal stability and surface smoothness of the material are further improved, and multifunctional compounding and weather resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ABS resins, and particularly to a modified ABS resin and a preparation method thereof. Background Art

[0002] ABS resin (acrylonitrile-butadiene-styrene copolymer, ABS is the abbreviation of Acrylonitrile Butadiene Styrene) is a thermoplastic polymer material with high strength, good toughness and easy processing and molding. Because of its high strength, corrosion resistance and high temperature resistance, it is often used to manufacture the plastic shell of instruments.

[0003] However, traditional ABS resins have the following limitations:

[0004] 1. Insufficient flame retardancy: Ordinary ABS resins are flammable, and a large amount of flame retardants need to be added to pass the UL94 standard. However, traditional halogen-based flame retardants have environmental problems, while phosphorus-nitrogen-based flame retardants, although environmentally friendly, easily lead to a decrease in the mechanical properties of materials (such as a decrease in tensile strength and impact toughness) and deterioration of processing fluidity;

[0005] 2. Contradiction between impact resistance and rigidity: Although toughening with a rubber phase can improve impact resistance, it will sacrifice the rigidity and surface hardness of the material, and it is particularly prone to brittle fracture in a low-temperature environment;

[0006] 3. Poor weather resistance: It is prone to aging and discoloration when exposed to ultraviolet rays or a humid and hot environment for a long time, affecting the product life.

[0007] In view of the above problems, there is an urgent need for a modified ABS resin and a preparation method thereof. Summary of the Invention

[0008] The purpose of the present invention is to provide a modified ABS resin and a preparation method thereof to solve the problems raised in the above background art.

[0009] To solve the above technical problems, the present invention provides the following technical solution: A modified ABS resin, comprising the following components by weight percentage:

[0010] ABS matrix resin 60% - 85%;

[0011] Organosilicon-modified acrylate core-shell toughening agent 5% - 15%;

[0012] Phosphorus-nitrogen-based composite flame retardant 8% - 20%;

[0013] Nanoscale titanium dioxide 0.5% - 3%;

[0014] Rare earth-based β nucleating agent 0.1% - 1.2%;

[0015] Hindered amine light stabilizer: 0.3% - 1.5%;

[0016] Among them, the phosphorus-nitrogen composite flame retardant is compounded by aluminum hypophosphite and melamine polyphosphate according to a mass ratio of 1:1.2 - 1:2.5, and the surface is modified by silane coupling agent KH-550.

[0017] Preferably, the acrylonitrile content of the ABS matrix resin is 22% - 28%, the particle size distribution of the butadiene rubber phase is in the range of 150 - 300 nm, and the melt flow rate (220 °C / 10 kg) is 15 - 35 g / 10 min.

[0018] Preferably, the core layer of the silicone-modified acrylate core-shell toughening agent is a polysiloxane cross-linked structure, the shell layer is a methyl methacrylate-butyl acrylate copolymer, its average particle size is 80 - 150 nm, and the silicone content accounts for 15% - 30% of the total mass of the toughening agent.

[0019] Preferably, the nanoscale titanium dioxide is anatase type, the average particle size is 20 - 50 nm, the surface is double-coated with stearic acid and vinyltrimethoxysilane, and is pretreated by ultraviolet irradiation for 2 - 4 hours.

[0020] A preparation method of a modified ABS resin, S1, premixing treatment: After vacuum drying the ABS matrix resin at 80 - 100 °C for 4 - 6 hours, premix it with the silicone-modified acrylate core-shell toughening agent and nanoscale titanium dioxide in a high-speed mixer at a rotation speed of 2000 - 3000 rpm for 5 - 8 minutes;

[0021] S2, flame retardant activation: Place the phosphorus-nitrogen composite flame retardant in a fluidized bed, introduce nitrogen for protection, heat up to 120 - 140 °C, and then atomize and spray into an ethanol solution of silane coupling agent KH-550, with a treatment time of 30 - 50 minutes;

[0022] S3, melt blending: Add the premix, the activated flame retardant, the rare earth β-nucleating agent, and the hindered amine light stabilizer to a twin-screw extruder, and control the processing temperature as follows:

[0023] Zone 1: 180 - 190 °C;

[0024] Zone 2: 200 - 210 °C;

[0025] Zone 3: 220 - 230 °C;

[0026] Zone 4: 225 - 235 °C;

[0027] Die head temperature: 210 - 220 °C;

[0028] The screw rotation speed is 350 - 450 rpm, and the vacuum degree is maintained at -0.06 - -0.08 MPa;

[0029] S4, Post - granulation treatment: After the extruded strip is cooled and pelletized by water, it is treated in a hot air circulation drying oven at 60 - 80 °C for 2 - 4 hours to obtain the finished modified ABS resin.

[0030] Preferably, the screw combination of the twin - screw extruder is configured as follows:

[0031] The conveying section uses a deep - groove forward - threaded element;

[0032] The mixing section includes 3 groups of 45° staggered - angle kneading blocks and 2 groups of reverse - threaded elements;

[0033] The devolatilization section is provided with two exhaust ports and is equipped with a melt pump pressure - stabilizing device;

[0034] The length ratio of each functional section is 3:5:2.

[0035] Preferably, in the pre - mixing treatment stage, 0.05% - 0.2% of the quaternary ammonium salt - type surfactant antistatic agent of the premix is added, and liquid carbon dioxide is injected three times during the mixing process for low - temperature impact modification.

[0036] Preferably, in the ethanol solution of the silane coupling agent KH - 550, the concentration of KH - 550 is 8% - 12% wt, the ethanol is anhydrous ethanol, the atomizing pressure is controlled at 0.3 - 0.5 MPa, and the liquid spraying rate is 15 - 25 mL / min.

[0037] Preferably, in the post - treatment stage, a stepped cooling process is adopted:

[0038] In the first stage, the temperature is decreased to 120 °C at a rate of 8 - 10 °C / min;

[0039] In the second stage, the temperature is decreased to 80 °C at a rate of 5 - 6 °C / min;

[0040] In the third stage, it is naturally cooled to room temperature;

[0041] The whole process is carried out under the protection of a nitrogen atmosphere.

[0042] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0043] First, in the present invention, a phosphorus - nitrogen - based flame retardant composed of aluminum hypophosphite and melamine polyphosphate (mass ratio 1:1.2 - 1:2.5) is used. Through surface modification with a silane coupling agent to improve dispersibility, while achieving efficient flame retardancy (UL94 V - 0 to V - 1 level), it inhibits melt dripping and reduces the impact on mechanical properties. Through an organosilicon - modified acrylate core - shell toughening agent (core layer polysiloxane / shell layer MMA - BA copolymer), the low - temperature impact resistance is improved (notched impact ≥ 15 - 25 kJ / m 2) while avoiding rigidity loss, balancing tensile strength (≥45MPa) and toughness, and optimizing the synergistic flame retardancy and mechanical properties; nano-titanium dioxide is double-coated with stearic acid and silane and pre-treated with ultraviolet light to significantly enhance the dispersibility and ultraviolet shielding performance (UVA transmittance <5%), combined with hindered amine light stabilizer (HALS), the material has a strength retention rate of ≥90% after 1000 hours of QUV aging, and the crystal structure is optimized by rare earth β-nucleating agents, further improving the thermal stability and surface finish of the material, thereby improving the multifunctional composite and weather resistance.

[0044] Second, the present invention, through the fluidized bed activation flame retardant, the step-by-step cooling process and the twin-screw extruder segmented temperature control (180-235°C), ensures the uniform dispersion of components and interface compatibility, the melt flow rate (15-35g / 10min) is adjustable, and is suitable for complex thin-wall injection molding, wherein Example 1: Balanced performance (UL94 V-1 level, notched impact ≥15kJ / m 2 ), suitable for general scenarios such as home appliance casings; Example 2: high fluidity (MFR ≥ 30g / 10min) and low smoke characteristics (smoke density reduced by 30%), suitable for automobile dashboards and rail transit interiors; Example 3: extreme flame retardancy (UL94 V-0 level, LOI ≥ 32%) and super weather resistance, meeting the needs of outdoor electrical equipment and automotive battery casings.

[0045] Third, the present invention, the halogen-free flame retardant system complies with environmental regulations, and the trace addition (0.05% to 0.2%) of the antistatic agent (quaternary ammonium salt type) effectively reduces the surface resistance (10 9 ~10 11 Ω), reducing the additional post-processing cost, and optimizing the component ratio (such as no antistatic agent is added in Example 3), which can reduce the cost in a targeted manner and adapt to different market demands. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A flow chart was prepared for the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The present invention provides the following technical solutions:

[0049] Embodiment 1

[0050] See also Figure 1, A modified ABS resin, with the following weight percentage ratios:

[0051] ABS matrix resin (acrylonitrile 24%, butadiene particle size 200 nm, MFR 20 g / 10 min): 70%;

[0052] Organic silicon modified acrylate core-shell toughening agent (core layer polysiloxane, shell layer MMA-BA, particle size 100 nm, organic silicon content 20%): 10%;

[0053] Phosphorus-nitrogen based compound flame retardant (aluminum hypophosphite: MPP = 1:1.5, total addition amount 12%): 12%;

[0054] Nano-titanium dioxide (anatase type, particle size 30 nm, double-coated, UV treated for 2 h): 1.5%;

[0055] Rare earth β nucleating agent (model NX-8000): 0.5%;

[0056] Hindered amine light stabilizer (HALS-622): 0.8%;

[0057] Antistatic agent (quaternary ammonium salt type): 0.2%.

[0058] A preparation method of the modified ABS resin:

[0059] Premixing treatment:

[0060] The ABS resin is vacuum dried at 80 °C for 4 hours, and premixed with the toughening agent and nano-TiO 2 at 2000 rpm for 5 minutes;

[0061] Inject liquid CO 2 in three portions (10 mL each time) for low-temperature impact modification.

[0062] Flame retardant activation:

[0063] The flame retardant is passed through nitrogen in a fluidized bed, and atomized and sprayed into a 10% KH-550 ethanol solution at 130 °C (atomization pressure 0.3 MPa, rate 20 mL / min) for 40 minutes.

[0064] Melt blending:

[0065] Twin-screw extruder parameters:

[0066] Temperature: zone 1 185 °C, zone 2 205 °C, zone 3 225 °C, zone 4 230 °C, die head 215 °C;

[0067] Screw rotation speed 400 rpm, vacuum degree -0.07 MPa;

[0068] Screw combination: Feeding section (deep groove thread): Kneading section (3 sets of kneading blocks + 2 reverse threads): Devolatilization section = 3:5:2.

[0069] Post-treatment:

[0070] The extruded strip is cooled with water and pelletized, and dried with hot air at 70°C for 3 hours;

[0071] Stepwise cooling: 10°C / min → 120°C → 5°C / min → 80°C → Natural cooling (protected by nitrogen).

[0072] For the modified ABS resin prepared in this example, its ratio characteristics:

[0073] ABS matrix resin (70%): Medium acrylonitrile content (24%), balancing rigidity (acrylonitrile) and toughness (butadiene);

[0074] Silicone toughening agent (10%): Core-shell structure enhances impact resistance and prevents low-temperature embrittlement;

[0075] Phosphorus-nitrogen flame retardant (12%, aluminum hypophosphite: MPP = 1:1.5): Synergistic flame retardancy, inhibits dripping, suitable for general flame retardant requirements;

[0076] Nano-TiO 2 (1.5%): Double coating enhances dispersibility and provides basic UV protection;

[0077] Antistatic agent (0.2%): Reduces surface charge accumulation, suitable for scenarios such as electronic enclosures;

[0078] Comprehensive effects:

[0079] Balanced performance: Considering mechanical strength (tensile strength ≥ 45 MPa), flame retardancy (UL94 V-1), impact resistance (notched impact ≥ 15 kJ / m 2 ) and processing fluidity;

[0080] Applicable scenarios: General-purpose flame retardant materials such as home appliance casings and office equipment.

[0081] Example 2

[0082] Please refer to Figure 1 , a modified ABS resin, with the following ratio by weight percentage:

[0083] ABS matrix resin (acrylonitrile 26%, butadiene particle size 250 nm, MFR 25 g / 10 min): 75%;

[0084] Silicone-modified acrylate toughening agent (particle size 120 nm, silicone content 25%): 8%;

[0085] Phosphorus-nitrogen based flame retardant (aluminum hypophosphite: MPP = 1:2, total addition amount 10%): 10%;

[0086] Nano-TiO 2 (particle size 40nm, UV treated for 3h): 2%;

[0087] Rare earth β nucleating agent: 0.8%;

[0088] Hindered amine light stabilizer: 1.0%;

[0089] Antistatic agent: 0.2%.

[0090] Preparation method of a modified ABS resin:

[0091] Premixing treatment:

[0092] The ABS resin is dried at 90°C for 5 hours, and is premixed with a toughening agent and TiO 2 at 2500 rpm for 6 minutes;

[0093] Liquid CO 2 is injected in three times (15 mL each time).

[0094] Flame retardant activation:

[0095] Spray in a 12% KH-550 ethanol solution at 135°C (pressure 0.4 MPa, rate 18 mL / min), and treat for 35 minutes.

[0096] Melt blending:

[0097] Extrusion temperature: zone 1 190°C, zone 2 210°C, zone 3 230°C, zone 4 235°C, die head 220°C;

[0098] Screw speed 450 rpm, vacuum degree -0.08 MPa.

[0099] Post-treatment:

[0100] Dry at 80°C for 4 hours;

[0101] Stepwise cooling: 8°C / min → 120°C → 6°C / min → 80°C → natural cooling.

[0102] For the modified ABS resin produced by this example, its ratio characteristics:

[0103] ABS matrix resin (75%): high acrylonitrile (26%) and high melt flow rate (25 g / 10 min), improving fluidity and surface finish;

[0104] Organic silicon toughening agent (8%): reducing the amount of toughening agent used and avoiding excessive sacrifice of rigidity;

[0105] Phosphorus-nitrogen flame retardant (10%, aluminum hypophosphite: MPP = 1:2): Focus on gas-phase flame retardancy (high MPP ratio), inhibiting smoke generation;

[0106] Nano-TiO 2 (2%): Extend the UV treatment time (3h), enhancing light stability;

[0107] Antistatic agent (0.2%): Maintain a low surface resistance (10 9 ~10 11 Ω).

[0108] Comprehensive effects:

[0109] High processability: The melt flowability is improved (MFR≥30g / 10min), suitable for complex thin-walled injection molded parts;

[0110] Low-smoke flame retardancy: The smoke density during combustion is reduced by more than 30% (ASTM E662), applicable to the interior of rail transit;

[0111] Applicable scenarios: Precision components such as automotive instrument panels and electronic connectors.

[0112] Example 3

[0113] Please refer to Figure 1 , a modified ABS resin, proportioned by weight percentage:

[0114] ABS matrix resin (acrylonitrile 28%, butadiene particle size 280nm, MFR 30g / 10min): 65%;

[0115] Silicone toughening agent (particle size 150nm, silicone content 30%): 15%;

[0116] Phosphorus-nitrogen flame retardant (aluminum hypophosphite: MPP = 1:2.5, total addition amount 18%): 18%;

[0117] Nano-TiO 2 (particle size 50nm, UV treatment 4h): 3%;

[0118] Rare earth β nucleating agent: 1.0%;

[0119] Hindered amine light stabilizer: 1.5%.

[0120] A preparation method of a modified ABS resin:

[0121] Premixing treatment:

[0122] The ABS resin is dried at 100°C for 6 hours, and premixed with the toughening agent and TiO 2 at 3000rpm for 8 minutes;

[0123] Without adding antistatic agent and liquid CO 2 .

[0124] Flame retardant activation:

[0125] Spray 8% KH-550 solution at 140 °C (pressure 0.5 MPa, rate 25 mL / min), and treat for 50 minutes.

[0126] Melt blending:

[0127] Extrusion temperature: Zone 1: 180 °C, Zone 2: 200 °C, Zone 3: 220 °C, Zone 4: 225 °C, Die head: 210 °C;

[0128] Screw speed 350 rpm, vacuum degree -0.06 MPa.

[0129] Post-treatment:

[0130] Dry at 60 °C for 2 hours;

[0131] Stepwise cooling: 9 °C / min → 120 °C → 5 °C / min → 80 °C → Natural cooling.

[0132] The modified ABS resin prepared by this example has the following ratio characteristics:

[0133] ABS matrix resin (65%): Low content but high butadiene particle size (280 nm), enhancing the toughness foundation;

[0134] Silicone toughening agent (15%): Maximum toughening ratio, significantly enhancing low-temperature impact resistance (impact retention rate at -30 °C ≥ 80%);

[0135] Phosphorus-nitrogen flame retardant (18%, aluminum hypophosphite: MPP = 1:2.5): High addition amount + high MPP ratio, achieving UL94 V-0 level flame retardancy;

[0136] Nano-TiO 2 (3%): Maximum addition amount + longest UV treatment (4 h), providing strong antibacterial property and UV shielding (UVA transmittance < 5%);

[0137] Without adding antistatic agent: Sacrificing antistatic property, reducing cost, for non-sensitive environments.

[0138] Comprehensive effect:

[0139] Ultimate performance:

[0140] Optimal flame retardancy (LOI ≥ 32%, vertical burning self-extinguishing time ≤ 3 s);

[0141] Outstanding toughness (notched impact ≥ 25 kJ / m 2 );

[0142] Excellent weather resistance (strength retention rate ≥ 90% after 1000h of QUV aging);

[0143] Applicable scenarios: outdoor electrical equipment, automotive battery casings with high flame retardancy requirements.

[0144] The differential test results of the processability, flame retardancy, toughness, and weather resistance of the modified ABS resins prepared in Example 1, Example 2, and Example 3 are as follows:

[0145]

[0146] As can be seen from the above table, Example 1 focuses on balanced performance, Example 2 improves processing fluidity, and Example 3 strengthens flame retardancy and toughening.

[0147] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principle and spirit, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A modified ABS resin, characterized in that: The following components are included by weight percentage: ABS matrix resin 60%~85%; 5% to 15% of silicone-modified acrylate core-shell toughening agent; Phosphorus-nitrogen composite flame retardant 8% to 20%; Nano-sized titanium dioxide 0.5% to 3%; Rare earth β nucleating agent 0.1% to 1.2%; Hindered amine light stabilizer 0.3% to 1.5%; The phosphorus-nitrogen composite flame retardant is compounded by aluminum hypophosphite and melamine polyphosphate in a mass ratio of 1:1.2 to 1:2.5, and the surface is modified by a silane coupling agent KH-550.

2. A modified ABS resin according to claim 1, characterized in that: The acrylonitrile content of the ABS matrix resin is 22% to 28%, the particle size distribution of the butadiene rubber phase is in the range of 150 to 300 nm, and the melt flow rate (220° C. / 10 kg) is 15 to 35 g / 10 min.

3. A modified ABS resin according to claim 1, characterized in that: The core layer of the organosilicon-modified acrylate core-shell toughener is a polysiloxane cross-linked structure, and the shell layer is a methyl methacrylate-butyl acrylate copolymer with an average particle size of 80-150nm. The organosilicon content accounts for 15%-30% of the total mass of the toughener.

4. A modified ABS resin according to claim 1, characterized in that: The nano-scale titanium dioxide is anatase-type with an average particle size of 20 to 50 nm. The surface is double-coated with stearic acid and vinyl trimethoxysilane and pre-treated with ultraviolet irradiation for 2 to 4 hours.

5. A method for preparing a modified ABS resin, wherein the raw material composition of the modified ABS resin is as described in claim 1, characterized in that: Preparation method used: S1, premixing treatment: after vacuum drying the ABS matrix resin at 80-100° C. for 4-6 hours, premix it with the organosilicon-modified acrylate core-shell toughening agent and nano-sized titanium dioxide in a high-speed mixer at a speed of 2000-3000 rpm for 5-8 minutes; S2, flame retardant activation: place the phosphorus-nitrogen composite flame retardant in a fluidized bed, introduce nitrogen protection, heat to 120-140°C, and then spray an ethanol solution of silane coupling agent KH-550 into the fluidized bed for 30-50 minutes; S3, melt blending: add the premix, activated flame retardant, rare earth β nucleating agent, and hindered amine light stabilizer into a twin-screw extruder, and control the processing temperature to: Zone 1: 180-190℃; Zone 2: 200-210℃; Zone 3: 220-230℃; Zone 4: 225-235°C; Head temperature 210~220℃; The screw speed is 350-450rpm, and the vacuum degree is maintained at -0.06-0.08MPa; S4, post-granulation treatment: After the extruded material strips are water-cooled and pelletized, they are treated in a hot air circulation drying oven at 60-80° C. for 2-4 hours to obtain a modified ABS resin product.

6. The method for preparing a modified ABS resin according to claim 5, characterized in that: The screw combination configuration of the twin-screw extruder is: The conveying section uses deep groove positive thread elements; The mixing section contains three sets of 45° staggered angle kneading blocks and two sets of reverse screw elements; The devolatilization section is equipped with double exhaust ports and a melt pump pressure stabilizing device; The length ratio of each functional segment is 3:5:

2.

7. The method for preparing a modified ABS resin according to claim 1, characterized in that: In the premixing stage, 0.05% to 0.2% of the premix is ​​added as an antistatic agent, a quaternary ammonium salt surfactant, and liquid carbon dioxide is injected three times during the mixing process for low-temperature impact modification.

8. The method for preparing a modified ABS resin according to claim 1, characterized in that: In the ethanol solution of the silane coupling agent KH-550, the concentration of KH-550 is 8% to 12% by weight, the ethanol is anhydrous ethanol, the atomization pressure is controlled at 0.3 to 0.5 MPa, and the spraying rate is 15 to 25 mL / min.

9. The method for preparing a modified ABS resin according to claim 1, characterized in that: In the post-processing stage, a step-by-step cooling process is adopted: In the first stage, the temperature is lowered to 120°C at a rate of 8-10°C / min; In the second stage, the temperature is lowered to 80°C at a rate of 5-6°C / min; The third stage is to cool naturally to room temperature; The whole process was carried out under the protection of nitrogen atmosphere.

Citation Information

Cited By

  • Enhanced high-flame-retardant ABS composite material as well as preparation method and application thereof

    CN122145963A